Synaptic Loss in Multiple Sclerosis: A Systematic Review of Human Post-mortem Studies - Möck, E. E. Amelie; Honkonen, Eveliina; Airas, Laura (Frontiers in Neurology, 2021)
Background: Gray matter pathology plays a central role in the progression of multiple sclerosis. The occurrence of synaptic loss appears to be an important but, to date, still poorly investigated aspect of MS pathology. In this systematic review, we want to draw together the recent knowledge about synaptic loss in human post-mortem studies. Methods: We conducted a systematic search with PubMed to identify relevant publications. Publications available by the15th June 2021 were taken into account. We selected human post-mortem studies that quantitatively assessed the synapse number in MS tissue. Results: We identified 14 relevant publications out of which 9 reported synaptic loss in at least one investigated subregion. The most commonly used synaptic marker was synaptophysin nonetheless, we found substantial differences in the methodology and the selection of reference tissue. Investigated regions included the cortex, the hippocampus, the cerebellum, the thalamus and the spinal cord. Conclusion: Synaptic loss seems to take place throughout the entire central nervous system. However, the results are inconsistent, probably due to differences in the methodology. Moreover, synaptic loss appears to be a dynamic process and thus the nature of this pathology might be captured using in vivo synaptic density measurements.